The movement of popular hawzi poetry in the Tlemcen region (Ibn Sahla Boumediene as a model) - benabdallah, fethallah (The Notebooks of the Algerian Poetics Laboratory Journal, 2021)
This research paper attempts to achieve an inductive approach to Al-Hawzi folk poetry in the Tlemcen region, by standing on one of the poles of this poetry.. Ibn Sahla Boumediene Tlemceni through his poetry. As well as clarifying what was written about his life; and monitor the aesthetics and specifics of this type of poetry. The study begins in its analysis of the structure of some of its texts, poetry, and its various functions, from the necessity of approaching it horizontally in order to know its components and poetic glossary by relying on its investigating divan…